STUDENT-CENTERED LEARNING AND TESTING AS AN APPROACH TO DEVELOP STUDENTSâ PROFICIENCY ON ENGLISH SENTENCE STRUCTURE TO PROMOTE AUTONOMOUS LEARNING - Rahmawan, Andi Dian; Wiyanah, Sri (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2018)
This study investigates how Sentence Master downloaded from Android can be used as a self-study media for students to promote Autonomous Learning to develop studentsâ comprehension on English sentence structure which is grammatically correct. Students can measure, by themselves, whether the material given during the teaching and learning process has been successfully learned. The result of this study is also intended to be used by the teachers and lecturers to indicate the successfulness of teaching and learning that have been conducted. This is an action research which 10 students of English Education Program of the University of PGRI Yogyakarta were employed as the objects of the research. They are tested to run the game of Sentence Master and the score will be recorded that benefits teacher to consider whether the learning process that has been conducted is successful. This study also investigates studentsâ difficulty on making English sentence. This study emerges results that Sentence Master helps students to understand English grammar better by employing the smart phone to promote Autonomous Learning. This media is used by the students as the indication whether they have the abilities to make good English sentences.Â DOI:Â doi.org/10.24071/llt.2018.210204